PENDIDIKAN SARAPAN SEHAT MENUJU BANGSA SEHAT BERPRESTASI BAGI ANAK SEKOLAH DASAR NEGERI MAUK III KABUPATEN TANGERANG BANTEN - Ronitawati, Putri; Sa’Pang, Mertien; Sitoayu, Laras; Nuzrina, Rachmanida; Melani, Vitria; Dhyani S, Prita; Novianti, Anugerah (Universitas Esa Unggul, 2018)
AbstractIn the 6-12 year period, school-aged children are very sensitive in shaping their cognitive development. If during this period they experience hunger then the opportunity to study in school to be reduced (WFP 2006). One message Balanced Nutrition (message six), based on Permenkes No. 41/2014 is a habit of breakfast. Nutrition education accompanied by the provision of food in schools such as a healthy breakfast will run more effectively when walking in tandem. Healthy breakfast education activity aims to raise public awareness, especially school children about the importance of breakfast, the benefits of breakfast, the type of healthy breakfast, and snacks safe. This activity is held in order to commemorate World Health Day and National Education Day and aim to socialize healthy breakfast education activity for School Children at SDN Mauk III of Tangerang Regency of Banten. Socialization is done by providing nutrition education with comic media